Studi Literatur: Analisis Kemampuan Komunikasi Matematis Ditinjau Dari Gaya Belajar Siswa Smp Pada Materi Bangun Ruang Sisi Datar - Nadiva Dwi Anggani; Didi Suryadi; Nurjanah (Pergunu Jawa Barat, 2023)
The aim of this study was to describe the mathematical communication abilities reviewed from the learning styles of high school students on the building material of flat side spaces. This research uses a qualitative approach to the method of literary study. Based on the results of the study, it was found that students with visual learning styles often have high mathematical communication abilities because students with the visual learning style are able to connect real objects into the form of mathematics ideas, able to present mathematic ideas in the shape of symbols, capable in explaining ideas, everyday situations and the relationship of mathems in writing with images, able enough to understand and evaluate mathematically ideas in solving problems and able in communicating the conclusions of answers that correspond to the given problem. Students with an auditory learning style can meet indicators expressing mathematical ideas in the form of diagrams, using mathematics notation and symbols in presenting ideas and drawing conclusions from mathematic statements and students with kinesthetic learning styles can meet the indicator expressing the mathematological ideas in diagram form, using notations and symbol. Therefore, there is a need for advanced research to study further with more research, and conduct research offline so that more in-depth information is obtained.